Patient Engagement Survey Regarding Future Double-Blinded, Randomized Controlled Trial of Tapering of Chronic Opioid Therapy - Jared James; Benjamin Lai; Terrence Witt (SAGE Publishing, 2019)
Objective: There is a lack of evidence regarding tapering opioid medications in patients with chronic non-cancer pain. The purpose of this survey was to gather perspectives on future research into opioid tapering from utilizers of chronic opioid therapy (COT) or other people affected by chronic noncancer pain. Methods: The survey was distributed in paper form to patients on COT and via an online platform to patients self-enrolled in the chronic pain patient engagement group. The survey included a layman's description of a possible tapering trial of opioid medications and elicited binary responses regarding willingness to participate and reasoning as well as qualitative freeform responses. Thematic analysis was performed to identify themes in narrative responses. Results: A total of 190 surveys were returned with 72.1% of all respondents answering positively regarding their willingness to participate in a proposed study. The most common reasons for participating in the study included concerns regarding opioid dependence, adding to society's knowledge of opioid medications, and determining if the respondent would personally receive benefit from opioid medications. Patients recently on COT felt it was important to be able to withdraw from the study and return to usual care at any time (41.8% for recent COT and 15.5% for no recent COT, P < .05). The most common reason for unwillingness to participate was that respondents did not feel they had enough information to feel comfortable participating. The narrative responses showed a group of respondents felt COT was the only answer to their or their loved ones' chronic pain and that a study would demonstrate the need to continue these medications long-term. There were also stories of side effects and dependence with decreasing effectiveness of opioids for pain control. When prompted to comment on study design, respondents indicated the study should include alternative pain management options. This was accompanied by responses with the assumption that pain will worsen as opioid medications are decreased. Conclusion: Patient concerns regarding opioid medications and discontinuation reflect the lack of evidence available to prescribers. There appears to be patient support for future research into the effects of tapering opioid medications.